Influence of 'green school certification' on students' environmental literacy and adoption of sustainable practice by schools. (10th May 2018) - Goldman, Daphne; Ayalon, Ofira; Baum, Dorit; Weiss, Bell
Abstract: The whole-school approach to sustainability is recognized as a vital educational component for moving toward sustainable societies. 'Green-school certification' in Israel, as a whole-school sustainability program, integrates: changes in school operations, incorporating sustainability content in the curriculum and building links with local communities; aiming that sustainability become the students' mindset and the school's organizational culture. This study investigated the influence of this program on: 1) upper primary students' environmental literacy, using a closed and open-ended questionnaire; 2) incorporating sustainable practice in the schools' operations, using an 'environmental visibility' tool. Students' environmental literacy and the school's environmental performance were higher in schools that had moved to the advanced certification. Despite this, the educational gains lag behind achievements in the schools' environmental performance. Recycling is perceived as the foremost means for environmentally-responsible behavior and students do not relate between their personal materialistic consumption and its environmental consequences. This implies that the program needs to advance from 'light green' sustainability education to tackle consumption, as a major issue of modern society, from the more fundamental transitions required in lifestyles and values. Another major challenge is maintaining the school's long-term commitment to sustainability post-certification. Suggestions are provided for addressing these issues that may increase the contribution of this framework, as the educational channel for national SD policy, to promote sustainability. Highlights: Educational gains and improved environmental performance occur in schools accredited ongoing green Achievement in schools' environmental performance is greater than students' educational gains. Recycling is perceived (by schools and students) as a major channel for pro-environmental behavior. Students don't relate between personal materialistic consumption and its environmental impacts. A challenge to the certification is sustaining the school's long-term commitment to sustainability.